Alloying Pd with Cu boosts hydrogen production via room-temperature electrochemical water-gas shift reaction. (November 2022) - Wei, Huifang; Liu, Huan; Yu, Liang; Zhang, Mo; Zhang, Yunlong; Fan, Jinchang; Cui, Xiaoju; Deng, Dehui
Abstract: Room-temperature electrochemical water-gas shift (RT-EWGS) process provides a promising route for high purity hydrogen production under ambient conditions, in which the anodic carbon monoxide (CO) oxidation as the key and bottleneck-type reaction largely hinders the overall efficiency due to its sluggish reaction kinetics. It is of great significance to develop low cost and efficient anode electrocatalysts to enhance the hydrogen production via improving the CO oxidation activity, but it remains a great challenge. Herein, by alloying Pd with Cu, we achieve a high mass activity of 19.9 mA/mgPd for anodic CO oxidation at 0.3 V versus reversible hydrogen electrode ( vs. RHE), which is over 330 times higher than that over pure Pd catalyst and significantly higher than the previously reported catalysts. Combined with density functional theory calculations, we find that the adsorbed CO (CO*) species is more likely to react with the adsorbed OH (OH*) rather than the OH - in the solution for PdCu alloy catalyst during the anodic CO oxidation process, and the introduction of Cu into Pd renders a weakened CO* adsorption along with an enhanced OH* adsorption, which significantly lower the overpotential via optimizing the anodic oxidation of CO pathway. This work provides a new direction for the design of efficient anode catalysts toward RT-EWGS with low energy input. Graphical Abstract: Alloying Pd with Cu can significantly increase the hydrogen production from electrochemical water-gas shift process, in which the anodic oxidation of carbon monoxide activity is promoted via weakening the adsorbed CO adsorption along with enhancing the adsorbed OH adsorption on Pd sites. ga1 Highlights: Alloying Pd with Cu can significantly enhance the anodic CO oxidation in room-temperature electrochemical water-gas shift. The optimized Pd0.7 Cu catalyst delivers a much higher mass activity than all the previously reported catalysts. The introduction of Cu into Pd renders a weakened adsorbed CO adsorption along with an enhanced adsorbed OH adsorption. The introduction of Cu into Pd can effectively lower the overpotential via optimizing the anodic oxidation of CO pathway.